Association between the C-reactive protein-triglyceride glucose index and new-onset coronary heart disease among metabolically heterogeneous individuals - Yafang Chen; Wenjun Jia; Jianmin Guo; Han Yang; Xi Sheng; Liping Wei; Jiao Li (Cardiovascular Diabetology)
Abstract Background The C-reactive protein–triglyceride glucose index (CTI) integrates inflammatory and metabolic markers and is closely associated with the incidence of coronary heart disease (CHD) and hypertension. However, its clinical utility among metabolically heterogeneous populations remains unclear. This study aims to investigate the association between CTI and new-onset CHD and to assess the potential value of combining CTI with the C-reactive protein-albumin-lymphocyte (CALLY) index in improving the identification of such clinical diagnoses. Methods This study included 2237 participants, categorized into four obesity and metabolic phenotypes: metabolically healthy normal weight, metabolically healthy overweight/obese, metabolically unhealthy normal weight (MUNW), and metabolically unhealthy overweight/obese. The association between the CTI and new-onset CHD was analyzed using logistic regression, accounting for potential confounders. Subgroup analyses stratified by glucose metabolic states, age, and gender were performed, and multiple statistical methods were further employed to investigate the mediating role of the CALLY index and the incremental value of CTI in combination with the CALLY index for enhancing the identification of new-onset CHD. Results The analysis demonstrated a robust association between the CTI and new-onset CHD (P < 0.001), with the highest sensitivity observed in MUNW individuals. The CALLY index was identified as a partial mediator of this relationship, emphasizing the critical role of immune-inflammatory processes in CHD. Notably, individuals with a high CTI (≥ 9.887) and a low CALLY index (< 1.221) showed the strongest association with CHD diagnoses at admission (OR = 2.36, 95% CI: 2.06—2.69). The integration of the CTI and CALLY indices was significantly associated with a stronger discriminatory ability for new-onset CHD. Conclusion The CTI demonstrated a significant statistical association with new-onset CHD diagnoses among metabolically heterogeneous individuals. Its combination with the CALLY index further enhanced diagnostic discrimination, supporting its potential utility in individualized identification and refined clinical assessment.